Rutin attenuates vancomycin‐induced renal tubular cell apoptosis via suppression of apoptosis, mitochondrial dysfunction, and oxidative stress. (17th June 2019) - Qu, Shaoqi; Dai, Cunchun; Guo, Hui; Wang, Cuncai; Hao, Zhihui; Tang, Qihe; Wang, Haixia; Zhang, Yanping
Abstract : Vancomycin is a glycopeptide antibiotic widely used to treat infections caused by methicillin‐resistant Staphylococcus aureus . However, nephrotoxicity is a major adverse side effect, and the development of effective nephroprotective agents remains a priority in antimicrobial chemotherapy. In this study, we investigated the cell protective effects of the flavonol glycoside rutin against vancomycin‐induced toxicity. Vancomycin added to porcine renal tubular LLC‐PK1 cells caused an increase of production of intracellular reactive oxygen species and subsequent apoptotic cell death. Pretreatment of LLC‐PK1 cells with rutin at 5, 10, and 20 μM for 2 hr prior to 2‐mM vancomycin exposure for 24 hr significantly decreased intracellular reactive oxygen species and increased superoxide dismutase and catalase activities. Rutin pretreatment also protected cells from vancomycin‐induced caspase activation, mitochondrial membrane depolarization, and subsequent apoptosis. This study demonstrates a protective effect of rutin and suggests that rutin coadministration is an alternative therapy for treatment of vancomycin‐induced nephrotoxicity.